Best practices in European wetland restoration: a review of manuals and guidelines - Santaoja, Minna; Squires, Tom; Klimkowska, Agata; Mc Guinness, Shane; Granath, Gustaf; Törmänen, Tiina; Biedroń, Ilona; Terrisse, Arnaud (Springer Nature, 2025)
A significant portion of wetlands is currently degraded and scaling up restoration efforts is necessary for both biodiversity and climate targets. However, many barriers to ecological restoration have been identified. To overcome them, capacity building and effective exchange of best practices are vital. Restoration experts have reported shortcomings in the availability, usability, scope, and quality of restoration guidance and manuals. This study reviews wetland restoration guidance across Europe (and beyond), assesses the state-of-the-art and potential gaps, and discusses how well it addresses restoration impediments. The reviewed resources performed generally well in providing technical guidance for restoration, regardless of the wetland type addressed. The manuals also covered various aspects of restoration project planning generally well, but a striking shortcoming was that monitoring and post-restoration evaluation were rarely mentioned. Regarding stakeholder engagement, again many resources hardly addressed this aspect of restoration, but the most recent resources performed better. In the review, general restoration manuals, not specific to any wetland type, were ranked highest across the various aspects of restoration. At the same time, we want to highlight that manuals with a narrower scope serve their purpose well in their context. A key limiting factor for capacity building and cross-border knowledge exchange is language—many of the good restoration manuals were in national languages only. We recommend reserving resources in projects for making restoration guidance better accessible (e.g. English translation) and drawing on multidisciplinary expertise for upscaling the socio-ecological approach to restoration.
Keywords: capacity building; knowledge transfer; monitoring; peatlands; restoration manuals; socio-ecological approach